Apoptotic mechanism in human brain microvascular endothelial cells triggered by 4′-iodo-α-pyrrolidinononanophenone: Contribution of decrease in antioxidant properties. (1st February 2022) - Sakai, Yuji; Taguchi, Maki; Morikawa, Yoshifumi; Miyazono, Hidetoshi; Suenami, Koichi; Ochiai, Yuto; Yanase, Emiko; Takayama, Tomohiro; Ikari, Akira; Matsunaga, Toshiyuki
Graphical abstract: Highlights: 4′-Halogenation potently augments cytotoxicity evoked by α-pyrrolidinononanophenone. 4′-Iodo-α-pyrrolidinononanophenone (I-α-PNP) elicits cytotoxicity most potently. I-α-PNP induces apoptosis via the mitochondrial reactive oxygen species generation. Decrease in antioxidant properties is related to the apoptotic mechanism of I-α-PNP. Abstract: In this study, we newly synthesized four α-pyrrolidinononanophenone (α-PNP) derivatives [4′-halogenated derivatives and α-pyrrolidinodecanophenone (α-PDP)], and then performed the structure-cytotoxicity relationship analyses. The results showed the rank order for the cytotoxic effects, α-PNP < α-PDP < 4′-fluoro-α-PNP < 4′-chrolo-α-PNP < 4′-bromo-α-PNP < 4′-iodo-α-PNP (I-α-PNP), and suggest that cytotoxicities of 4′-halogenated derivatives were more intensive than that of elongation of the hydrocarbon chain (α-PDP). We also surveyed the apoptotic mechanism of I-α-PNP in brain microvascular endothelial (HBME) cells that are utilized as the in vitro model of the blood-brain barrier. HBME cell treatment with I-α-PNP facilitated the apoptotic events (caspase-3 activation, externalization of phosphatidylserine, and DNA fragmentation), which were almost completely abolished by pretreating with antioxidants. In addition, the immunofluorescent staining revealed the enhanced production of hydroxyl radical in mitochondria by the I-α-PNP treatment, inferring that the I-α-PNP treatment triggers the apoptotic mechanism dependent on the enhanced ROS production in mitochondria. The treatment with I-α-PNP increased the production of cytotoxic aldehyde 4-hydroxy-2-nonenal and decreased the amount of reduced glutathione. Additionally, the treatment decreased the 26S proteasome-based proteolytic activities and aggresome formation. These results suggest that decrease in the antioxidant properties is also ascribable to HBME cell apoptosis elicited by I-α-PNP.